Kerley B lines in the lung apex – a distinct CT sign for pulmonary congestion (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY The purpose of this study was to establish a new computed tomography (CT) sign for pulmonary congestion (Kerley B lines in the lung apex in patients with cardiac or renal insufficiency) and to find the best signs to differentiate between pulmonary congestion and interstitial lung disease (ILD). METHODS 180 consecutive patients undergoing CT were retrospectively included: 43 patients with cardiac, 17 with renal and 30 with mixed cardiac/renal insufficiency. In addition, we selected 90 patients with known ILD (usual interstitial pneumonia and nonspecific interstitial pneumonia). The cases were retrieved by means of a full text search of radiological reports and electronic patient files. The cardiothoracic ratio and diameters of the superior and inferior vena cava were measured. Pleural effusion, peribronchial cuffing, Kerley B lines (interlobular septa), ground glass opacity (GGO) and consolidation were analysed for prevalence, distribution and quantity (1 to 3). Fisher’s exact and Mann-Whitney-test were applied using Bonferroni correction. RESULTS Kerley B lines in the lung apex were present in 81% and 76% of the cardiac and renal groups, respectively, which was significantly more than in the ILD group (26%, p